2017
DOI: 10.1039/c6ra28595c
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics insights into diabetes nephropathy and protective effects of Radix Scutellariae on rats using ultra-high performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry

Abstract: UHPLC-Q-TOF-MS based metabolomics combined with multivariate statistical analysis for evaluating protective effects ofRadix Scutellariaeon DN rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…The metabolism of aromatic amino acids, especially phenylalanine and tyrosine, was considered to be correlated with CKD and DN [62,63]. Changes in phenylalanine metabolism showed a close association with chronic kidney failure, including extensive urinary excretion of its down products [64].…”
Section: Discussionmentioning
confidence: 99%
“…The metabolism of aromatic amino acids, especially phenylalanine and tyrosine, was considered to be correlated with CKD and DN [62,63]. Changes in phenylalanine metabolism showed a close association with chronic kidney failure, including extensive urinary excretion of its down products [64].…”
Section: Discussionmentioning
confidence: 99%
“…This study showed for the first time that in untreated AKU there is alteration to tyrosine, purine and TCA cycle metabolites ( Figure 5). These data add to a growing body of evidence from metabolomic studies that perturbations in tyrosine, purine and energy metabolism are linked in numerous diseases including Alzheimer's (Kaddurah-Daouk et al, 2011, depression (Weng et al, 2015) and diabetic nephropathy (Men et al, 2017).…”
Section: Associated Alteration To Tyrosine Purine and Tca Cycle Metamentioning
confidence: 67%
“…The increased xanthosine and decreased 2,3-cyclic AMP and inosine 5'-monophosphate reported here for Hgd -/mice is consistent with a shift in purine catabolism in response to oxidative conditions induced by HGA and ochronosis, as xanthosine is a direct precursor for xanthine and uric acid. Xanthosine is increased in urine from rats with other oxidative diseases, including chronic kidney disease (Zhang et al, 2015) and diabetes nephropathy, and markedly decreased following administration of nephroprotective therapy (Men et al, 2017). The alteration in purine metabolism perhaps most associated with pathology is elevated uric acid, the classic example being gout, in which elevated blood uric acid is the direct cause of a painful arthropathy.…”
Section: Alteration To Purine Metabolismmentioning
confidence: 99%
“…5-HTP is the immediate precursor of serotonin, which has been shown to inhibit apoptosis in multiple immune cell types under inflammatory conditions 64 . In terms of 3-MDI, reports exist in the literature regarding its detection in rat urine 65 , serum 66 and human breath 67 , but its function in MSCs upon inflammatory stimulation is yet unclear.…”
Section: Resultsmentioning
confidence: 99%